Identifikasi Jenis Makroalga Yang Berpotensi Sebagai Antibakteri Di Perairan Pantai Dato Kabupaten Majene - Gaby Maulida Nurdin; Arlinda Puspitasari; Ariandi (Universitas Sulawesi Barat, 2023)
Macroalgae have various types of bioactive compounds that have potential as antibacterial. This study aims to determine the type of macroalgae that have the potential as an antibacterial in the waters of Dato Beach, Majene Regency. The research was conducted using cruising survey method by exploring the intertidal area of Dato Coastal Waters, Majene Regency. This study consisted of 3 (three) stages, namely the observation stage, sampling, identification stage based on morphology in the form of thallus color, thallus shape and branching type. and the stage of testing the potential of macroalgae as an antibacterial based on literature studies and phytochemical screening. The results showed that there were 9 species of macroalgae found in the intertidal area of Dato Beach consisting of 5 (five) types of brown algae (Ocrophyta), namely Turbinaria decurrens, Padina australis, Sargassum crispifolium, S. polycystum, S. oligocystum; 2 (two) types of red algae (Rhodophyta) Galaxaura rugosa, Acanthophora spicifera; 2 (two) types of green algae (Chlorophyta) Halimeda opuntia and H. macroloba. Of the 9 types of macroalgae found, 5 of them were positive for containing active compounds of flavonoids, steroids/triterpenoids and alkaloids. Meanwhile, 4 species of macroalgae were determined as antibacterial based on literature studies. Keywords— Identification, Macroalgae, Dato Beach